Community compliance with the covid-19 protocol hygiene policy in Klaten Regency, Indonesia - Hari Sutra Disemadi; Denis Oxy Handika (Faculty of Law, University of Muhammadiyah Malang, 2020)
The problem for all countries in the world, including Indonesia, is the presence of a virus originating from Wuhan City, China. This virus is known as COVID-19. The Government of Indonesia has established COVID-19 as a type of disease that causes a Public Health Emergency. Therefore, prevention efforts must be made in accordance with existing provisions. The research method used is a socio-legal research method with a normative legal approach and a sociological approach conducted in Klaten-Central Java. The results of this study indicate that the policy currently being taken is health quarantine. The policy is the issuance of health protocols for the community. This protocol is known as the COVID-19 hygiene protocol, one of which is related to the obligation to wear masks by everyone when outside the home and the Hand Washing with Soap (CPTS) movement with running water either/both the use of antiseptic hand sanitizers as stipulated in the Ministry of Health Circular Number HK.02.02/I/385/2020. The level of awareness and compliance in Klaten Regency on the policy is exceptionally well, indicated by the dominant number of people in the use of masks when they are outside of the house and washing their hands with soap with running water either/both using antiseptic hand sanitizers. Therefore, the existence of a health protocol as a government policy in accelerating COVID-19 countermeasures is expected by parties, such as the Regional Government and the community in playing an active role referring to those who are feverish to the nearest hospital. Then, the Regional Government can socialize or urge people to use masks. For emergencies, if you sneeze or cough in a public area, cover your mouth with your inner elbows or upper sleeve. People who are sick are also advised not to use public transportation to minimize the possible risk of spreading the disease.